Induction of Adventitious Bud Regeneration from Root Explants in Sambong (Blumea balsamifera (L.) DC.) - Xiaolu Chen , Yongfeng Xiao , Mei Huang , Zhenxia Chen , Chao Yuan , Dan Wang , Lingliang Guan , Li Liao , Xingfei Li , Yong Yang , Fulai Yu, (Forest Chemicals Review)
Root explants were used for the induction of adventitious bud regeneration in sambong (Blumea balsamifera (L.) DC.), and different medium formulas, such as different concentrations of Murashige and Skoog basal medium, 6-benzyladenine, naphthaleneacetic acid, and sucrose were compared for the effects in this research. The results showed that roots could be used as explants for high efficient induction of adventitious bud regeneration in sambong. The optimal medium composition for the induction of adventitious bud regeneration was Murashige and Skoog basal medium supplemented with 1.0 mg/L 6-benzyladenine, 0.05 mg/L naphthaleneacetic acid, and 30 g/L sucrose. In this study, we not only optimized the tissue culture system but also reduced the generation of chimeras in the process of tissue culture. The protocol established in the present experiment provides a technical basis for further research such as artificial induction of mutation and transgenic manipulation in sambong.